Donor anonymity: national legal regulation and international experience - I. I. Shpuhanych; K. Yu. Diukarieva-Berzhanina; O. S. Yavorska (Medičnì Perspektivi)
The article is devoted to the analysis of legal, medical, moral and ethical aspects of the principle of donor anonymity. The principle of anonymity has a legal framework and appropriate regulation in international documents. These are: Directive on standards of quality and safety of human organs intended for transplantation, WHO Guiding Principles on Human Cell, Tissue and Organ Transplantation, Convention for the protection of Human Rights and Dignity of the Human Being with regard to the Application of Biology and Medicine: Convention on Human Rights and Biomedicine and the Additional Protocol etc. This principle is the basis of the legislative regulation of donation in many countries, including Ukraine. The normative approaches to the legal regulation of donation and the principle of anonymity in accordance with national legislation are investigated. The Law of Ukraine "On the Application of Transplantation of Anatomical Materials to Man" bylaws and the application of the principle of anonymity depending on the type of donation: posthumous and lifetime are analyzed. The international experience of applying the principle of anonymity is characterized. The principle of absolute anonymity is enshrined, in particular, in the legislation of the Netherlands, Sweden. Accordingly, such regulatory approaches exclude any contact between the donor and the recipient. According to the principle of conditional anonymity (in particular, the United States and the United Kingdom), the exchange of information between the donor and the recipient is permitted, surely at the will. The advantages and disadvantages of direct communication between the donor and the recipient are described. The expediency of applying the principle of conditional anonymity in national practice is substantiated regarding moral, ethical, and psychological aspects. In order to implement this, it is proposed to consolidate the right of the donor and the recipient to approve or deny the data exchange at the legislative level. It is suggested to assign the appropriate functions aimed at facilitating the parties' interaction to the transplant coordinator.